Upaya Meningkatkan Minat Belajar Anak Desa Sukadadi, Kecamatan Gedong Tataan, Kabupaten Pesawaran Melalui Lomba Cerdas Tepat (LCT) - Farida; Destika Putri Fitriana; Ayu Puspitasari; Finka Indiyani; Firda Nurul Fadila; Riza Tri Handayani (Nuban Jaggadhita Center, 2023)
This service activity program aims to increase children's interest in learning in Sukadadi Village. Through the Accurate Smart Competition (LCT) activity, it is hoped that this initiative will provide children with an understanding of the systematic process of the Precise Smart Competition (LCT) and consequently enhance their interest in learning. The method employed in this service is the Participatory Action Research (PAR) method. The Accurate Smart Competition in this service comprises 2 rounds: the preliminary round and the final round. Participants included 7 TPAs in Sukadadi Village, with each group consisting of 3 individuals. Initially, 4 groups emerged from the preliminary round, advancing to compete in the final round. Eventually, TPAs 1, 4, 7, and 8 progressed to the final round. Subsequently, in the final round, TPA 9 secured the 1st place among the 4 groups. The outcomes of this service exhibit an increase in children's interest in learning in Village S. This is evidenced by the attendance of 7 out of 10 hamlets during the registration, as well as the enthusiastic participation of the children in the competition. Additionally, this service benefits the Serumpun Malay KKN students. Through this initiative, KKN students can foster interest in learning and identify the potential of every child in Sukadadi Village, Gedong Tataan District, Pesawaran Regency.